The ortho-semi-torsional (OST) spring analogy method for 3D mesh moving boundary problems - Markou, George; Mouroutis, Z.S.; Charmpis, D.C.; Papadrakakis, Manolis (My University, 2007)
In this paper a new mesh update technique is presented for the effective treatment of 3D mesh moving boundary problems. The proposed mesh update scheme utilizes an ortho-semi-torsional (OST) spring analogy concept to construct a fictitious elasticity problem with imposed boundary displacements, which is efficiently solved with an algorithm based on the preconditioned conjugate gradient (PCG) method. The PCG-based solution algorithm is also applied to three other mesh update techniques available in the literature, namely the torsional, the semi-torsional and the ball-vertex spring analogy schemes. The four spring analogy methods are comparatively assessed with respect to their robustness and computational efficiency in handling 3D benchmark problems, as well as more involved test cases such as the AGARD wing 445.6 and a 3D three-element airfoil. It is demonstrated that the OST spring analogy concept combined with a PCG-type algorithm for the solution of fictitious elasticity problems provides robustness for substantially distorted meshes and computational efficiency for large-scale problems. © 2006 Elsevier B.V. All rights reserved.
Keywords: Coupled problems; Mesh update; Solution algorithms; Preconditioned conjugate gradient